Increasing trends in Deep Infiltrating Endometriosis (DIE) with Bilateral Endometrioma from Adolescence till Menopause: Case Series (Bangladesh Journal of Obstetrics & Gynaecology, 2019)
Deep infiltrating endometriosis has varying clinical presentaions with certain diagnostic signs and symptoms. Bilateral endometriomas alongwith DIE has been observed in all the age groups in this series at more than 35 years of age.Bangladesh J Obstet Gynaecol, 2019; Vol. 34(2): 127-133